Could the Audiometric Criteria for Sudden Sensorineural Hearing Loss Miss Vestibular Schwannomas?. (28th May 2022) - Shilo, Shahaf; Hannaux, Ouriel; Gilboa, Dor; Ungar, Omer Jacob; Handzel, Ophir; Abu Eta, Rani; Muhanna, Nidal; Oron, Yahav
Abstract : Objective: To investigate the likelihood of missing a vestibular schwannoma (VS) diagnosis in patients who present with a sudden hearing loss (SHL) that does not meet the most accepted audiometric criteria for sudden sensorineural hearing loss (SSNHL) (a decrease of ≥30 dB at three consecutive frequencies). Methods: All adult patients (>18 years) diagnosed with SHL of any severity in a tertiary care referral medical center between 2015 and 2020 and who underwent an MRI scan to rule out VS were included. Statistical analyses were conducted to evaluate the difference between the rate of VS among patients with an initial audiogram, which met the abovementioned criteria, and those who did not. Other audiometric criteria for SNHL were also evaluated (≥10 dB at ≥2 frequencies and ≥ 15 dB at one frequency). Results: Of the 332 patients included in the study, 152 met the audiometric criteria for SSNHL, and 180 did not. Both groups had a similar VS rate (8.6% vs. 8.9%, p  = 0.914). Similar results were found when other audiometric criteria for asymmetric SNHL were analyzed. In a subgroup analysis of patients with VS‐associated SSNHL, neither the tumor size nor the Koos classification was associated with any of the audiometric criteria systems. Conclusion: There should be a high index of suspicion for the presence of VS in patients with an SHL of any severity. Level of Evidence: 3 Laryngoscope, 133:670–675, 2023 Abstract : Patients with sudden hearing loss whose audiograms did not meet the formal audiometric criteria for sudden sensorineural hearing loss were found to have a similar rate of vestibular schwannoma as those who did. Therefore, we advocate a high index of suspicion of a concomitant vestibular schwannoma with sudden hearing loss of any severity, and urge our colleagues to consider referring those patients to an MRI scan regardless of the hearing loss severity.